27 CANDIDA TROPICALIS INFECTION MODULATES THE GUT MICROBIOME IN DSS-INDUCED COLITIS IN C57BL/6 MICE. (7th February 2019) - Di Martino, Luca; Buttò, Ludovica F; Hager, Christopher; Ghannoum, Mahmoud; Osme, Abdullah; Pizarro, Theresa; Cominelli, Fabio
Abstract: Background: Infections (candidiasis) caused by Candida spp. including C. tropicalis, have dramatically increased worldwide, indicating that this organism is an emerging pathogenic yeast. Our recent studies indicate that C. tropicalis is significantly higher in Crohn's disease (CD) patients than in their non-disease first-degree relatives. However, the role of C. tropicalis in exacerbating intestinal inflammation in patients with CD has not been fully elucidated. The aim of the present study was to determine the effect(s) of C. tropicalis infection on intestinal inflammation following acute intestinal injury induced by dextran sodium sulfate (DSS) and its effect on modulation of gut microbiome in mice. Methods: Colitis was studied in C57BL/6 mice by endoscopy, histology, stereomicroscopy and 16s analysis. Mice were infected with C. tropicalis by oral gavage (1x10 7 cells/100 µl PBS) once daily for three days. Colitis was induced by administration of 2.5% DSS in drinking water for 7 days. Fecal samples were collected before and after the infection. After 14 days of recovery with only drinking water, mice were sacrificed and colons and fecal samples were collected. Results: C57BL/6 mice infected with C. tropicalis showed no differences in colonoscopy scores at day 7 compared to control, uninfected mice. However, increased severity of colitis vs. uninfected mice (endoscopy score: 21 days 7.033 ± 0.204 (infected) vs. 5.575 ± 0.528 (uninfected), P< 0.05, n=13/group) was noted at day 21. Histological analysis of colon showed that mice infected with C. tropicalis were more susceptible to develop DSS-induced colitis compared to uninfected mice (histology score: 21 days 5.647 ± 0.852 (uninfected) vs. 9.885 ± 1.357 (infected), P <0.05; n≥13/group). Stereomicroscopy analysis of colon showed a trend of higher scores in infected mice compared to uninfected mice (% affected areas: 21 days 14.0 ± 1.6 (uninfected) vs. 17.5 ± 2.1 (infected), P =ns; n=6/group). 16s and beta diversity analysis of DNA extracted from fecal samples showed that before the infection, the two groups of mice had comparable microbiome ( P =ns), but after the candida infection the intestinal microbiome composition in the two groups experienced significant changes ( P <0.05). In particular, after the infection Akkermansia muciniphila was more abundant in the feces of the infected mice compared to the uninfected ones ( P <0.05). Conclusion: Our data demonstrate that C. tropicalis may play a pro-inflammatory role in intestinal injury by exacerbating gut inflammation during the recovery phase of DSS-induced colitis. We speculate that infection with the fungus C. tropicalis may play a role in triggering flares by modifying the gut microbiome of IBD patients.